The potential of gallic acid and ascorbic acid as green reducing agent in ZnO nanoparticle synthesis - Norlin, Pauzi; Norashikin, Mat Zain; Nurul Amira, Ahmad Yusof (Dept. of Chemistry, UTM, 2018)
In this study, method for the synthesis of zinc oxide (ZnO) nanoparticles for biomedical applications ideally involve the use of nontoxic, less hazardous reducing and capping agent as well as the selection of environmentally benign solvents. In this study, we had investigated the potential of gallic acid and ascorbic acid as both reducing and capping agent in a green approach using microwave heating method. Two parameters including microwave power (400W and 800W) and time of heating (4 and 8 min) were investigated. UV-Vis absorption spectrum showed a typical spectrum for ZnO nanoparticles around 300nm wavelength. This microwave heating method with green reducing and capping agent successfully been advocated as a possible environmentally friendly alternative to chemical methods in synthesizing ZnO nanoparticles. ZnO nanoparticles synthesis from gallic acid and ascorbic acid were both found to exhibit antibacterial activity against a Gram-positive bacterium Bacillus subtilis and a Gram-negative bacterium Escherichia coli.